Classification of circulation patterns during the formation and dissipation of continuous pollution weather over the Sichuan Basin, China. (15th February 2020) - Sun, Yu; Niu, Tao; He, Jianjun; Ma, Zhenfeng; Liu, Ping; Xiao, Dixiang; Hu, Junfeng; Yang, Jingchao; Yan, Xiaolu
Abstract: Pollution weather may cause serious damages to human life and property. Meteorological conditions like large-scale circulation can affect the formation and dissipation of pollution weather. We apply the hierarchical clustering method to classify circulation patterns based on the National Centers for Environmental Prediction (NCEP) Final Operational Global Analysis (FNL) sea level pressure (SLP) daily data and investigate their features during the formation and dissipation process of the defined 31 continuous pollution weather (CPW) cases in the Sichuan Basin using the meteorological data from 104 surface observation stations during 2007–2017. We find that the Sichuan Basin during the formation process is controlled by the large scale high-pressure circulation at sea level, and the SLP can be divided into high-pressure front type FC1 (32%) with the high pressure located in the west of the Basin, weak high-pressure type FC2 (35%) with the weak high pressure located in the Basin, and uniform pressure field type FC3 (33%) with the near homogeneous pressure distributed in the Basin. The Sichuan Basin during the dissipation process is dominated by the low-pressure circulation at sea level, and the SLP can be classified as low-pressure type DC1 (35%) with the low pressure centralize in the Basin, low-pressure front type DC2 (38%) with the low pressure center in the west of the Basin, and low-pressure bottom type DC3 (27%) with the low pressure in the north of the Basin. Besides, the wind, relative humidity, geopotential height, and temperature data are used to explore the formation and dissipation mechanisms of the CPW. The wind speed and temperature are lower during the formation phase of the CPW compared to those from the dissipation phase. Furthermore, we estimate the effects of the CPW on pollutants based on the air quality index and Particulate Matter (PM10 and PM2.5 ) concentration from environmental protection monitoring data during 2013–2017. The FC2 type shows the strongest enhancement of pollutants (36%), and the DC3 circumstance generates the most efficient scavenging mechanism to dispel pollutants (−57%). Highlights: The continuous pollution weather over the Sichuan Basin is defined in our study. Long term haze and fog data are used to identify the continuous pollution weather. Clustering analysis is applied to classify the circulation patterns. The characteristics of each circulation pattern are investigated. The impact of continuous pollution weather on the pollutants are quantified.